Glass article and method of making the same
Patent Information
- Application Number
- CN202011637295.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-03
- Filing Date
- 2020-12-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2040-12-31
AI Technical Summary
[0005]然而,如果应用于盖窗的玻璃制品具有小的厚度以减轻弯曲应力,则抗裂性可能降低
Smart Images

Figure CN113156680B_ABST
Abstract
Description
[0001] This application claims priority to and benefits derived therefrom of Korean Patent Application No. 10-2020-0000881, filed on January 3, 2020, the entire contents of which are incorporated herein by reference. Technical Field
[0002] This invention relates to glass products and methods for manufacturing the same. Background Technology
[0003] Glass products are widely used in electronic devices, including display equipment, and building materials. For example, glass products are used as substrates for flat panel display devices such as liquid crystal displays, organic light-emitting displays, or electrophoretic displays, or as cover windows used to protect display devices.
[0004] Foldable display devices for user convenience have been studied. Glass used in foldable display devices can have a small thickness to reduce bending stress when the display device is folded.
[0005] However, if the glass used for window covers has a small thickness to reduce bending stress, its crack resistance may be reduced. Summary of the Invention
[0006] Exemplary embodiments of the present invention provide glass articles having good compressive stress and small thickness.
[0007] Another exemplary embodiment of the present invention provides a display device comprising a glass article having good compressive stress and a small thickness.
[0008] Another exemplary embodiment of the present invention provides a method for manufacturing glass articles having good compressive stress and small thickness.
[0009] Another exemplary embodiment of the present invention provides an electric field application device for use in a method of manufacturing a glass article having good compressive stress and a small thickness.
[0010] However, the aspects of this disclosure are not limited to those set forth herein. These and other aspects of this disclosure will become more apparent to those skilled in the art upon reference to the following detailed description of the disclosure.
[0011] According to an exemplary embodiment, the glass article includes a first surface, a second surface opposite to the first surface, a first compression region extending from the first surface to a first compression depth in the thickness direction of the glass article, a second compression region extending from the second surface to a second compression depth in the thickness direction, and a tension region disposed between the first compression depth and the second compression depth, wherein the stress distribution of the first compression region includes a first point and a first inflection point, the first inflection point being located between the first point and the first surface, the depth from the first surface to the first point being about 45% to about 55% of the first compression depth from the first surface, the stress at the first point being greater than about 50% of the compressive stress at the first surface, and the thickness of the glass article being about 0.01 to about 0.05 millimeters (mm).
[0012] In an exemplary embodiment, when the stress distribution is plotted as a curve with the x-axis representing the thickness direction and the y-axis representing the stress value, the stress distribution in the first compression region may bulge upwards.
[0013] In an exemplary embodiment, the first compression depth may be in the range of about 8 micrometers (μm) to about 12 μm, and the compressive stress at the first surface may be in the range of about 800 megapascals (MPa) to about 1100 MPa.
[0014] In an exemplary embodiment, the stress at the first inflection point may be about 60% or more of the compressive stress at the first surface.
[0015] The glass article may also include a first side surface located between the first surface and the second surface, a first chamfered surface located between the first side surface and the first surface, and a second chamfered surface located between the first side surface and the second surface.
[0016] In an exemplary embodiment, the stress distribution in the first compression region may be symmetrical with the stress distribution in the second compression region.
[0017] Glassware may also include hydrogen ions and hydrated hydrogen ions.
[0018] Glass articles may also include impurities, wherein the content of the impurities is about 0.02% by weight (wt%) or higher, and the impurities may include copper ions, iron ions or tin ions.
[0019] In an exemplary embodiment, the first compression depth of the first compression region may be greater than the second compression depth of the second compression region, and the magnitude of the compressive stress at the first surface may be greater than the magnitude of the compressive stress at the second surface.
[0020] According to another exemplary embodiment, a glass article includes a first surface, a second surface opposite to the first surface, a first compression region extending from the first surface to a first compression depth in the thickness direction of the glass article, a second compression region extending from the second surface to a second compression depth in the thickness direction, and a tension region disposed between the first compression region and the second compression region, wherein the stress distribution of the first compression region includes a first point and a first inflection point, the first inflection point is located between the first point and the first surface, the depth from the first surface to the first point is about 45% to about 55% of the first compression depth from the first surface, the stress at the first point is greater than about 50% of the compressive stress of the first surface, the first compression depth of the first compression region is greater than the second compression depth of the second compression region, and the magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface.
[0021] In an exemplary embodiment, the glass article may be formed sequentially by an electric field application operation and a chemical tempering operation, wherein in the electric field application operation, a cathode (negative voltage) is applied to a first surface and an anode (positive voltage) is applied to a second surface.
[0022] According to yet another exemplary embodiment, the display device includes a display panel having a plurality of pixels, a cover window disposed on the display panel, and an optically transparent adhesive layer disposed between the display panel and the cover window. The cover window includes a first surface, a second surface opposite to the first surface, a first compression region extending from the first surface to a first compression depth in the thickness direction of the cover window, a second compression region extending from the second surface to a second compression depth in the thickness direction, and a tension region disposed between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point, the first inflection point being located between the first point and the first surface, the depth from the first surface to the first point being approximately 45% to approximately 55% of the first compression depth from the first surface, the stress at the first point being greater than approximately 50% of the compressive stress of the first surface, and the thickness of the cover window being approximately 0.01 to approximately 0.05 mm.
[0023] In an exemplary embodiment, when the stress distribution is shown as a graph where the x-axis represents the thickness direction and the y-axis represents the stress value, the stress distribution in the first compression region may be upwardly convex, the first compression depth is in the range of about 8 μm to about 12 μm, the compressive stress at the first surface is in the range of about 800 MPa to about 1100 MPa, and the stress at the first inflection point is about 60% or more of the compressive stress at the first surface.
[0024] In an exemplary embodiment, the first compression depth of the first compression region may be greater than the second compression depth of the second compression region, and the magnitude of the compressive stress at the first surface may be greater than the magnitude of the compressive stress at the second surface.
[0025] According to yet another exemplary embodiment, a method for manufacturing a glass article is provided, the method comprising: forming a glass sheet with a thickness of about 0.01 to about 0.05 mm; concentrating sodium ions on the surface of the glass sheet; and chemically tempering the glass sheet having sodium ions concentrated on the surface of the glass sheet.
[0026] In an exemplary embodiment, concentrating sodium ions on the surface of a glass slide may include a high-temperature / high-humidity treatment performed under temperature conditions of about 80 degrees Celsius to about 90 degrees Celsius, humidity conditions of about 80% to about 90% and a time of about 4 hours or less.
[0027] In an exemplary embodiment, concentrating sodium ions on the surface of a glass slide may include heat treatment performed at a temperature of about 600 degrees Celsius to about 700 degrees Celsius and for a time of about 4 hours or less.
[0028] In an exemplary embodiment, the surface of the glass sheet may include a first surface and a second surface opposite to the first surface, and the concentration of sodium ions on the surface of the glass sheet includes an electric field application operation in which a cathode (negative voltage) is applied to the first surface and an anode (positive voltage) is applied to the second surface.
[0029] In an exemplary embodiment, during the electric field application operation, the electric field can be applied to the glass plate in a temperature-controlled room.
[0030] In an exemplary embodiment, the temperature inside the chamber during the electric field application operation can be in the range of about 0 degrees Celsius to about 400 degrees Celsius, and the magnitude of the electric field applied during the electric field application operation can be in the range of about 100 volts / cm (V / cm) to about 200 V / cm.
[0031] In an exemplary embodiment, during the electric field application operation, an electric field may be applied to the glass sheet in a silicone oil bath.
[0032] According to yet another exemplary embodiment, a method for manufacturing a glass article is provided, the method comprising: forming a glass sheet including a first surface and a second surface opposite to the first surface; performing an electric field application operation, wherein a negative voltage is applied to the first surface and a positive voltage is applied to the second surface in the electric field application operation; and chemically tempering the glass sheet.
[0033] In an exemplary embodiment, an electric field applying device may be used to perform an electric field applying operation, and the electric field applying device may include a negative plate electrode that applies a negative voltage to a first surface and a positive plate electrode that applies a positive voltage to a second surface.
[0034] In an exemplary embodiment, during the electric field application operation, an electric field can be applied to the glass plate in a temperature-controlled room, where the temperature can be in the range of about 600 degrees Celsius to about 700 degrees Celsius, and the magnitude of the electric field applied during the electric field application operation can be in the range of about 100 V / cm to about 200 V / cm.
[0035] In an exemplary embodiment, the heat supply line may be connected to the negative electrode and the positive electrode respectively to provide heat.
[0036] In an exemplary embodiment, the electric field application operation may further include: placing a glass sheet between the negative electrode and the positive electrode, wherein each of the negative electrode, the positive electrode, and the glass sheet may be provided in multiples, the negative electrode and the positive electrode may be arranged alternately, and when placing the glass sheet, the glass sheet may be placed between the alternately arranged negative electrode and the positive electrode.
[0037] In an exemplary embodiment, each of the negative and positive electrode plates of the electric field applying device is rotatable, thereby extending horizontally during glass plate placement and vertically when an electric field is applied after glass plate placement.
[0038] In an exemplary embodiment, each of the negative electrode and the positive electrode is movable in a horizontal or vertical direction.
[0039] In an exemplary embodiment, the electric field application operation may further include: placing a glass sheet between the negative electrode and the positive electrode, wherein each of the negative electrode and the positive electrode may be provided as a single sheet and the glass sheet may be provided as a plurality of sheets, and when placing the glass sheet, the glass sheets may be arranged parallel to each other between the negative electrode and the positive electrode.
[0040] In an exemplary embodiment, each of the negative voltage and the positive voltage may include a direct current (DC) waveform, an alternating current (AC) waveform, a pulsed DC waveform, or a periodic AC (radio frequency (RF)) waveform.
[0041] According to another exemplary embodiment, the glass article includes a first surface, a second surface opposite to the first surface, a first compression region extending from the first surface to a first compression depth in the thickness direction of the glass article, a second compression region extending from the second surface to a second compression depth in the thickness direction, and a tension region disposed between the first compression region and the second compression region, wherein the stress distribution of the first compression region is asymmetrical with the stress distribution of the second compression region, and the magnitude of the compressive stress at the first surface is different from the magnitude of the compressive stress at the second surface.
[0042] In an exemplary embodiment, the magnitude of the compressive stress at the first surface may be greater than the magnitude of the compressive stress at the second surface.
[0043] In an exemplary embodiment, the first compression depth of the first compression region may be greater than the second compression depth of the second compression region.
[0044] According to yet another exemplary embodiment, a display device includes a display panel having a plurality of pixels, a cover window disposed on the display panel, and an optically transparent adhesive layer disposed between the display panel and the cover window. The cover window includes a first surface, a second surface opposite to the first surface, a first compression region extending from the first surface to a first compression depth in the thickness direction of the cover window, a second compression region extending from the second surface to a second compression depth in the thickness direction, and a tension region disposed between the first compression region and the second compression region. The stress distribution in the first compression region is asymmetrical with the stress distribution in the second compression region, the magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface, the second surface is in contact with the optically transparent adhesive layer, and the first surface is located outside the second surface.
[0045] The display device can be foldable, and when operated in the folded state, the display device can be folded so that portions of the second surface face each other and a tensile force is applied.
[0046] In an exemplary embodiment, the first compression depth of the first compression region may be greater than the second compression depth of the second compression region.
[0047] According to yet another exemplary embodiment, the electric field applying device includes a negative plate electrode and a positive plate electrode opposite to the negative plate electrode, wherein a glass sheet including a first surface and a second surface opposite to the first surface is placed between the negative plate electrode and the positive plate electrode, the negative plate electrode is configured to apply a negative voltage to the first surface, and the positive plate electrode is configured to apply a positive voltage to the second surface.
[0048] In an exemplary embodiment, the magnitude of the electric field applied to the glass sheet by the negative electrode and the positive electrode can be in the range of about 100 V / cm to about 200 V / cm.
[0049] In an exemplary embodiment, the electric field applying device may further include heat supply lines connected to the negative electrode and the positive electrode, respectively, wherein the heat supply lines are configured to apply heat to the negative electrode and the positive electrode, respectively.
[0050] In an exemplary embodiment, each of the negative electrode, the positive electrode, and the glass sheet may be configured as multiple, the negative electrode and the positive electrode may be arranged alternately, and the glass sheet may be placed between the alternately arranged negative electrode and the positive electrode.
[0051] In an exemplary embodiment, each of the negative electrode and the positive electrode may be rotatable.
[0052] In an exemplary embodiment, each of the negative electrode and the positive electrode is movable in a horizontal or vertical direction.
[0053] In an exemplary embodiment, each of the negative electrode and the positive electrode may be configured as a single plate, and multiple glass plates may be configured, with the glass plates arranged parallel to each other between the negative electrode and the positive electrode.
[0054] In an exemplary embodiment, the glass protective layer may be further disposed between the negative electrode plate and the positive electrode plate, and may also be disposed between adjacent glass sheets within the glass sheet.
[0055] In an exemplary embodiment, each of the negative voltage and the positive voltage may include a DC waveform, an AC waveform, a pulsed DC waveform, or a periodic AC (RF) waveform.
[0056] In an exemplary embodiment, the coating may be further disposed on the surface of the negative electrode facing the adjacent positive electrode and on the surface of the positive electrode facing the adjacent negative electrode.
[0057] In an exemplary embodiment, the coating may include an electrode material.
[0058] In an exemplary embodiment, the coating may include an electrode protective layer, and the electrode protective layer may include a dielectric. Attached Figure Description
[0059] These and / or other aspects will become apparent and more readily understood from the following description of exemplary embodiments taken in conjunction with the accompanying drawings, wherein:
[0060] Figure 1 It is a perspective view of a glass article according to various exemplary embodiments;
[0061] Figure 2 This is a cross-sectional view showing an example in which a glass article according to an exemplary embodiment is used as a cover window of a display device;
[0062] Figure 3 This is a cross-sectional view of a flat glass article according to an exemplary embodiment;
[0063] Figure 4 This is a schematic diagram illustrating an ion exchange process according to an exemplary embodiment;
[0064] Figure 5 It shows the basis Figure 3 A graph illustrating the stress distribution of a glass article according to an exemplary embodiment;
[0065] Figure 6 It is a graph showing the relationship between the distribution of potassium ions and compressive stress;
[0066] Figure 7 yes Figure 5 A magnified curve near the first compression region;
[0067] Figure 8 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment;
[0068] Figure 9 It shows from Figure 8 A schematic diagram illustrating a series of operations from cutting to tempering;
[0069] Figure 10 Detailed Figure 9 High temperature / high humidity treatment operation;
[0070] Figure 11 It is a graph showing the ion concentration around the surface of a glass article before a high-temperature / high-humidity treatment operation;
[0071] Figure 12 It is a graph showing the ion concentration around the surface of a glass article after a high-temperature / high-humidity treatment operation;
[0072] Figure 13 This is a cross-sectional view of a flat glass article according to an exemplary embodiment;
[0073] Figure 14 It shows the basis Figure 13 A graph illustrating the stress distribution of a glass article according to an exemplary embodiment;
[0074] Figure 15 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment;
[0075] Figure 16 Detailed explanation based on Figure 15 The heat treatment operation of an exemplary embodiment;
[0076] Figure 17 yes Figure 16 A magnified view of region A;
[0077] Figure 18 It shows the basis Figure 15 A graph showing the distribution of sodium ions before and after the heat treatment operation of an exemplary embodiment;
[0078] Figure 19 It shows the basis Figure 15 A graph showing the distribution of potassium ions during tempering before and after the heat treatment operation of an exemplary embodiment.
[0079] Figure 20This is a cross-sectional view of a glass article according to an exemplary embodiment;
[0080] Figure 21 yes Figure 20 Enlarged sectional view;
[0081] Figure 22 It shows the basis Figure 20 A graph illustrating the stress distribution of a glass article according to an exemplary embodiment;
[0082] Figure 23 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment;
[0083] Figure 24 The following details the implementation of the electric field application device according to an exemplary embodiment. Figure 23 An exemplary embodiment of the electric field application operation;
[0084] Figure 25 yes Figure 24 A magnified view of region B;
[0085] Figure 26 The following details the implementation of the electric field application device according to an exemplary embodiment. Figure 23 An exemplary embodiment of the electric field application operation;
[0086] Figure 27 This illustrates the application of an electric field using an exemplary embodiment of the device. Figure 23 The glass placement operation in the electric field application operation of an exemplary embodiment;
[0087] Figure 28 The movement of an electric field applying device according to an exemplary embodiment is shown;
[0088] Figure 29 The following details the application of an electric field using an exemplary embodiment of the device. Figure 23 An exemplary embodiment of the electric field application operation;
[0089] Figure 30 The following details the application of an electric field using an exemplary embodiment of the device. Figure 23 An exemplary embodiment of the electric field application operation; and
[0090] Figure 31 The following details the implementation of the electric field application device according to an exemplary embodiment. Figure 23 An exemplary embodiment of the electric field application operation. Detailed Implementation
[0091] As used herein, the term "glass article" refers to an article made wholly or partially of glass.
[0092] The specific structural and functional descriptions of exemplary embodiments of the present invention disclosed herein are for illustrative purposes only. The present invention can be implemented in many different forms without departing from its spirit and distinctive features. Therefore, exemplary embodiments of the present invention are disclosed for illustrative purposes only and should not be construed as limiting the invention. That is, the present invention is defined only by the scope of the claims.
[0093] It will be understood that when an element is referred to as being related to another element, such as being “connected” or “linked” to another element, it may be directly connected to or linked to the other element, or there may be an intermediate element between them. Conversely, it should be understood that when an element is referred to as being related to another element, such as being “directly connected” or “directly linked” to another element, there is no intermediate element. Other expressions explaining the relationship between elements, such as “between,” “directly between,” “adjacent,” or “directly adjacent,” should be interpreted in the same way.
[0094] Throughout the specification, the same reference numerals will denote the same or similar parts.
[0095] It will be understood that although the terms “first,” “second,” “third,” etc., may be used herein to describe various elements, components, regions, layers, and / or parts, these elements, components, regions, layers, and / or parts should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or part from another. Therefore, without departing from the teachings of this document, the first element, component, region, layer, or part discussed below may be referred to as the second element, component, region, layer, or part.
[0096] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. As used herein, “a,” “an,” “the,” and “at least one” do not indicate a limitation on quantity but are intended to include both the singular and the plural unless the context clearly indicates otherwise. For example, “element” has the same meaning as “at least one element” unless the context clearly indicates otherwise. “At least one” should not be construed as limiting “a” or “an.” “Or” means “and / or.” As used herein, the term “and / or” includes any and all combinations of one or more of the associated listed items. It will be further understood that the terms “comprising” and / or “including” as used in this specification specify the presence of the stated features, areas, integrals, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, areas, integrals, steps, operations, elements, components, and / or combinations thereof.
[0097] Furthermore, relative terms, such as “below” or “bottom” and “above” or “top”, are used herein to describe the relationship between one element and another as shown in the figures. It will be understood that, in addition to the orientations shown in the figures, relative terms are intended to include different orientations of the device. For example, if the device in one of the figures is flipped, an element described as being “below” the other element would then be oriented “above” the other element. Thus, the exemplary term “below” can include both “below” and “above” orientations, depending on the specific orientation of the figure. Similarly, if the device in one of the figures is flipped, an element described as being “below” or “under” the other element would then be oriented “above” the other element. Thus, the exemplary term “below” or “under” can include both “above” and “below” orientations.
[0098] As used herein, “about” or “approximately” includes the value stated and means within an acceptable range of deviation from the particular value as determined by one of ordinary skill in the art, taking into account the measurement discussed and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, “about” may mean within one or more standard deviations of the value stated, or within ±30 percent (%), 20%, 10%, or 5%.
[0099] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms, such as those defined in commonly used dictionaries, shall be interpreted as having a meaning consistent with their meaning in the context of the relevant art and in this disclosure, and shall not be interpreted in an idealized or overly formalized sense unless expressly defined herein.
[0100] Exemplary embodiments are described herein with reference to schematic cross-sectional views as idealized exemplary embodiments. Thus, variations in shape as a result of, for example, manufacturing techniques and / or tolerances, are expected. Therefore, the exemplary embodiments described herein should not be construed as limited to the specific region shapes shown herein, but are to include, for example, shape deviations due to manufacturing processes. For example, regions shown or described as flat may generally have rough and / or non-linear characteristics. Furthermore, acute angles shown may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the exact shape of the regions, nor are they intended to limit the scope of the claims.
[0101] In the following description, exemplary embodiments of the invention will be described with reference to the accompanying drawings.
[0102] Figure 1 These are perspective views of glass articles 100 to 103 according to various exemplary embodiments.
[0103] Glass is used in electronic devices including displays (such as tablet PCs, laptop PCs, smartphones, e-book readers, televisions, and PC monitors) and in refrigerators and washing machines that include displays, as a cover for protecting the display, a substrate for display panels, a substrate for touch panels, and optical components such as light guide plates. Glass is also used in vehicle dashboard covers, solar cell covers, building interior materials, and windows for buildings or houses.
[0104] Some types of glass require high strength. For example, glass used in windows needs to be thin to have high transmittance and light weight, but strong enough to be resistant to breakage from external impacts. Glass with increased strength can be manufactured using methods such as chemical tempering or thermal tempering. Figure 1 Examples of tempered glass with various shapes are shown in the image.
[0105] Reference Figure 1 In an exemplary embodiment, the glass article 100 may be in the shape of a flat sheet or plate. In an exemplary embodiment, the glass articles 101 to 103 may have a three-dimensional shape including curved portions. For example, the glass article may include a flat portion with curved edges (see glass article 101), may be bent entirely (see glass article 102), or may be folded (see glass article 103).
[0106] Each of the glass articles 100 to 103 may have a rectangular planar shape. However, each of the glass articles 100 to 103 according to the present invention is not limited to a rectangular planar shape. In another exemplary embodiment, each of the glass articles 100 to 103 may also have various planar shapes, such as rectangles, squares, circles, and ellipses with rounded corners.
[0107] In the exemplary embodiments described below, a flat plate having a rectangular planar shape will be described as an example of each of the glass articles 100 to 103.
[0108] Each of glass articles 100 to 103 includes a first surface US and a second surface RS opposite to the first surface US. The first surface US may be the upper surface of each of glass articles 100 to 103, and the second surface RS may be the lower surface of each of glass articles 100 to 103. Each of glass articles 100 to 103 may also include a side surface SS, and may also include a first chamfered surface CHS1 connecting each side surface SS and the first surface US, and a second chamfered surface CHS2 connecting each side surface SS and the second surface RS. A plane extending therefrom of the first surface US or the second surface RS may intersect (e.g., may be orthogonal to) a plane extending therefrom of any of the side surfaces SS. A plane extending therefrom of any of the chamfered surfaces CHS1 and CHS2 may not be parallel to the extending plane of the first surface US or the second surface RS or the extending plane of any of the side surfaces SS.
[0109] Figure 2 This is a cross-sectional view showing an example of a glass article 100 used as a cover window for a display device 500 according to an exemplary embodiment. Here, the glass article 100 is referred to as cover window 100.
[0110] Reference Figure 2 The display device 500 may include a display panel 200, a cover window 100 disposed on the display panel 200, and an optically transparent adhesive layer 300 disposed between the display panel 200 and the cover window 100 to bond the display panel 200 and the cover window 100 together.
[0111] The display panel 200 may be, for example, a self-emissive display panel, such as an organic light-emitting display panel (OLED), an inorganic electroluminescent (EL) display panel, a quantum dot light-emitting display panel (QED), a micro light-emitting diode (LED) display panel, a nano LED display panel, a plasma display panel (PDP), a field emission display panel (FED), or a cathode ray tube (CRT) display panel, or it may be a light-receiving display panel, such as a liquid crystal display (LCD) panel or an electrophoretic display (EPD) panel.
[0112] The display panel 200 may include a plurality of pixels PX, and an image may be displayed using light emitted from each pixel PX. The display device 500 may also include a touch sensor (not shown). In an exemplary embodiment, the touch sensor may be built into (embedded) in the display panel 200. For example, the touch sensor may be directly disposed on a display component of the display panel 200, such that the display panel 200 itself can perform touch functionality. In an exemplary embodiment, the touch sensor may be manufactured separately from the display panel 200 and then attached to the upper surface of the display panel 200 via an optically transparent adhesive layer.
[0113] A cover window 100 is disposed on the display panel 200. The cover window 100 protects the display panel 200. A reinforced glass article 100 may serve as the body of the cover window 100. The size of the cover window 100 may be larger than the size of the display panel 200. Therefore, the side surfaces of the cover window 100 may protrude more outward than the side surfaces of the display panel 200, but this is not limited to exemplary embodiments according to the present invention. The cover window 100 may also include a printed layer disposed on at least one surface of the glass article 100 at its edge. The printed layer of the cover window 100 may prevent the bezel area of the display device 500 from being visible from the outside and may perform a decorative function in some cases.
[0114] An optically clear adhesive layer 300 is disposed between the display panel 200 and the cover window 100. The optically clear adhesive layer 300 secures the cover window 100 to the display panel 200. The optically clear adhesive layer 300 may include an optically clear adhesive (OCA) or an optically clear resin (OCR).
[0115] The tempered glass product 100 described above will now be described in more detail.
[0116] Figure 3 This is a cross-sectional view of a flat glass article 100 according to an exemplary embodiment.
[0117] Reference Figure 3 The glass article 100 may include a first surface US, a second surface RS, a side surface SS, a first chamfered surface CHS1, and a second chamfered surface CHS2. The first surface US and the second surface RS of the flat glass article 100 are main surfaces with large areas. The first chamfered surface CHS1 connects each side surface SS and the first surface US, and the second chamfered surface CHS2 connects each side surface SS and the second surface RS.
[0118] The first surface US and the second surface RS are opposite each other in the thickness direction. When the glass article 100 is used to transmit light, such as a cover window of a display, light can typically be incident on either the first surface US or the second surface RS, and then transmitted to the other surface.
[0119] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may be, but is not limited to, a range of 0.01 to 2 millimeters (mm). In an exemplary embodiment, the thickness t of the glass article 100 may be about 0.05 mm or less. In an exemplary embodiment, the thickness t of the glass article 100 may be greater than about 0.05 mm and less than 2 mm. In an exemplary embodiment, the thickness t of the glass article 100 may be greater than about 0.01 mm and less than 0.05 mm. The glass article 100 may have a uniform thickness t. However, the exemplary embodiments of the present invention are not limited to this, and in the exemplary embodiments, the glass article 100 may also have a different thickness t in each region.
[0120] Glass article 100 can be tempered to have a predetermined stress distribution therein. Tempered glass article 100 is better protected against crack growth, crack propagation, and fracture due to external impact than untempered glass article 100. The tempered glass article 100 can have different stresses in different regions. For example, a first compression region CSR1 and a second compression region CSR2, in which compressive stress acts, can be located near the surface of the glass article 100, i.e., near the first surface US and the second surface RS. A tensile region CTR, in which tensile stress acts, can be located within the glass article 100. At the boundary between each of the first compression region CSR1 and the second compression region CSR2 and the tensile region CTR, the stress value can be zero. The compressive stress in one of the first compression region CSR1 and the second compression region CSR2 can have different stress values depending on the location (i.e., the depth from the surface). Furthermore, the tensile region CTR can have different stress values depending on the depth from the surface US or RS.
[0121] The positions of the first compression region CSR1 and the second compression region CSR2 in the glass article 100, the stress distribution in the first compression region CSR1 and the second compression region CSR2, and the compressive energy of the first compression region CSR1 and the second compression region CSR2 or the tensile energy of the tensile region CTR greatly affect the mechanical properties of the glass article 100, such as surface strength. This will be described in detail later.
[0122] The first compression zone CSR1 and the second compression zone CSR2 resist external impacts to prevent the growth of cracks in the glass article 100 or the breakage of the glass article 100. Furthermore, the compressive stress in the first compression zone CSR1 and the second compression zone CSR2 effectively prevents cracks (even if they grow) from propagating at their respective depths.
[0123] The first compression depth DOC1 is the thickness of the first compression region CSR1, and the second compression depth DOC2 is the thickness of the second compression region CSR2. The first compression depth DOC1 and the second compression depth DOC2 prevent cracks or grooves formed in the first surface US and the second surface RS from propagating to the tensile region CTR within the glass article 100. The greater the first compression depth DOC1 and the second compression depth DOC2, the better the crack propagation is prevented.
[0124] As described above, the thickness t of the glass article 100 can be about 0.05 mm or less. When the glass article 100 has a small thickness, the first compression depth DOC1 and the second compression depth DOC2 of the formed first compression region CSR1 and second compression region CSR2 can also be small. According to an exemplary embodiment, each of the first compression depth DOC1 and the second compression depth DOC2 can be about 0.01 mm or less. In this case, cracks or grooves may easily propagate to the tensile region CTR within the glass article 100.
[0125] However, even if the first compression depth DOC1 and the second compression depth DOC2 of the first compression region CSR1 and the second compression region CSR2 of the thin glass article 100 are small, the compressive stress at a specific depth of the first compression region CSR1 and the second compression region CSR2 can prevent cracks or grooves from propagating to the tensile region CTR.
[0126] The stress distribution of the aforementioned glass article 100 can be formed by tempering involving an ion exchange process.
[0127] Figure 4 This is a schematic diagram illustrating an ion exchange process according to an exemplary embodiment. Figure 4 The image shows the exchange of sodium ions for potassium ions within the glass. Tempering can be either thermal tempering or chemical tempering. In cases such as... Figure 3 In the case of a thin glass article 100 with a thickness of 0.05 mm or less in an exemplary embodiment, chemical tempering can be applied to achieve precise stress distribution control.
[0128] Reference Figure 4 Chemical tempering can be achieved through ion exchange. Ion exchange is a process that replaces ions within the glass with other ions. It allows ions located on or near the glass surface to be replaced or exchanged for larger ions with the same valence or oxidation state. For example, when the glass contains monovalent alkali metals such as Li+ or Na+, the monovalent cations on the surface can be exchanged for K+, Rb+, or Cs+, which have larger ionic radii.
[0129] When a glass containing sodium ions is exposed to potassium ions, for example by immersing the glass in a soluble salt bath containing potassium nitrate, the sodium ions inside the glass can be released to the outside, and potassium ions can replace the sodium ions. The potassium ions replacing the sodium ions generate compressive stress because the ionic radius of potassium ions is larger than that of sodium ions. The greater the amount of potassium ions, the greater the compressive stress. Since ion exchange occurs through the glass surface, the amount of potassium ions can be greatest at the glass surface (rather than inside the glass). As some of the potassium ions diffuse into the glass, they can increase the depth of the compression zone (i.e., the compression depth). However, the amount of potassium ions generally decreases with increasing distance from the surface. Therefore, the glass can have a stress distribution in which the compressive stress is greatest at the surface and gradually decreases in the direction toward the interior of the glass. However, the exemplary embodiments of the present invention are not limited to the above examples, and in another exemplary embodiment, the stress distribution can vary depending on the temperature, time, number of ion exchange processes, the presence or absence of heat treatment, etc.
[0130] Reference Figure 5 and Figure 6 The first compression zone CSR1 and the second compression zone CSR2 of the glass article 100 are described in detail.
[0131] Figure 5 It shows the basis Figure 3 A graph showing the stress distribution of a glass article 100 according to an exemplary embodiment. Figure 6 It is a graph showing the relationship between the distribution of potassium ions and compressive stress.
[0132] exist Figure 5 In the curve graph, the x-axis represents the thickness direction of the glass product 100, and the y-axis represents the stress value. Figure 5 In this specification, compressive stress is represented by positive values, while tensile stress is represented by negative values. The magnitudes of compressive stress / tensile stress represent the absolute values, regardless of their signs.
[0133] exist Figure 6 In the curve graph, the x-axis represents the distance from the surface of the glass product to 100, and the y-axis represents the concentration of potassium ions and the distribution of compressive stress.
[0134] Reference Figure 5 and Figure 6 The glass article 100 includes a first compression region CSR1 extending from a first surface US to a first compression depth DOC1 and a second compression region CSR2 extending from a second surface RS to a second compression depth DOC2. A tensile region CTR is disposed between the first compression depth DOC1 and the second compression depth DOC2. In the total stress distribution in the glass article 100, the regions on the two surfaces US and RS are symmetrical to each other with respect to the center in the thickness t direction. Although in Figure 5 Although not shown, the compression and stretching regions can also be arranged in a similar manner between the opposing side surfaces SS of the glass article 100.
[0135] The first compression region CSR1 and the second compression region CSR2 resist external impacts to prevent crack growth or breakage in the glass article 100. The greater the first maximum compressive stress CS1 of the first compression region CSR1 and the second maximum compressive stress CS2 of the second compression region CSR2, the greater the strength of the glass article 100. Since external impacts are typically transmitted through the surface of the glass article 100, it is advantageous for durability to have a first maximum compressive stress CS1 and a second maximum compressive stress CS2 at the first surface US and the second surface RS of the glass article 100. At this point, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 tend to be maximum at the surface and gradually decrease in the direction toward the interior of the glass article 100. That is, the first maximum compressive stress CS1 is the maximum stress that the first surface US can withstand, and the second maximum compressive stress CS2 is the maximum stress that the second surface RS can withstand.
[0136] The first compression depth DOC1 and the second compression depth DOC2 prevent cracks or grooves formed in the first surface US and the second surface RS from propagating into the tensile region CTR within the glass article 100. The larger the first compression depth DOC1 and the second compression depth DOC2, the better the crack propagation is prevented. The points corresponding to the first compression depth DOC1 and the second compression depth DOC2 correspond to the boundaries between the first compression region CSR1 and the second compression region CSR2 and the tensile region CTR, and have a stress value of 0.
[0137] Throughout the glass article 100, the tensile stress in the tensile region CTR can be balanced with the compressive stress in the first compression region CSR1 and the second compression region CSR2. That is, the total compressive stress (i.e., compressive energy) in the glass article 100 is equal to the total tensile stress (i.e., tensile energy). The stress energy accumulated in a region of predetermined width along the thickness t direction in the glass article 100 can be calculated by integrating the stress distribution. When the stress distribution in the glass article 100 of thickness t is represented by the function f(x), the following relationship can be established.
[0138]
[0139] As the tensile stress within the glass article 100 increases, when the glass article 100 breaks, fragments may be violently ejected and may shatter from within the glass article 100. The maximum tensile stress that satisfies the brittleness criterion of the glass article 100 may, but is not limited to, satisfy the following relationship.
[0140] CT1≤-38.7×ln(t)+48.2 (2)
[0141] In some exemplary embodiments, the maximum tensile stress CT1 may be 100 MPa or less, or it may be 85 MPa or less. A maximum tensile stress CT1 of 75 MPa or greater can improve mechanical properties, such as strength. In exemplary embodiments, the maximum tensile stress CT1 may be between 75 MPa and 85 MPa.
[0142] The maximum tensile stress CT1 of the glass article 100 is typically located in the central portion of the glass article 100 in the thickness t direction. For example, the absolute value of the maximum tensile stress CT1 of the glass article 100 may be located at a depth of 0.4t to 0.6t, a depth of 0.45t to 0.55t, or a depth of about 0.5t.
[0143] The stress distribution in the first compression region CSR1 and the second compression region CSR2 of the glass article 100 can be upwardly convex. The upwardly convex stress distribution in the first compression region CSR1 and the second compression region CSR2 can be provided by potassium ions, wherein sodium ions are ion-exchanged into potassium ions during the chemical tempering process.
[0144] Reference Figure 6 The concentration distribution of potassium ions from the first surface US and the second surface RS of the glass article 100 in the thickness direction is generally similar to the stress distribution of the first compression region CSR1 and the second compression region CSR2 of the glass article 100.
[0145] In other words, sodium ions to be exchanged can be concentrated on the first surface US and the second surface RS of the glass article 100, and the sodium ions concentrated on the first surface US and the second surface RS can be exchanged for potassium ions through chemical tempering. Therefore, since sodium ions are more concentrated on the first surface US and the second surface RS of the glass article 100 before chemical tempering, the ion exchange between sodium ions and potassium ions can be further promoted, and an upwardly convex stress distribution can be formed in the first compression region CSR1 and the second compression region CSR2, wherein the compressive energy of the first compression region CSR1 and the second compression region CSR2 is increased.
[0146] Reference Figure 7 The stress distribution in compression region CSR1 or CSR2 is described in detail below. The stress distribution in the first compression region CSR1 will be described in detail below. Since the stress distributions in the first compression region CSR1 and the second compression region CSR2 are symmetrical to each other, a repeated description of the stress distribution in the second compression region CSR2 will be omitted or briefly given.
[0147] Figure 7 yes Figure 5 A magnified curve near the first compression region CSR1.
[0148] exist Figure 7 In the examples, sample #1 represents a glass article 100 formed according to an exemplary embodiment by concentrating sodium ions to be ion-exchanged on a first surface US and a second surface RS of the glass article 100 and by performing chemical tempering in which the sodium ions concentrated on the first surface US and the second surface RS are exchanged for potassium ions, and sample #2 represents a comparative sample having the same glass composition as the glass article 100 according to an exemplary embodiment before concentrating sodium ions to be ion-exchanged on the first surface US and the second surface RS of the glass article 100 and being chemically tempered under the same conditions as the glass article 100 according to an exemplary embodiment.
[0149] Reference Figure 7 The stress distribution in the first compression region CSR1 of sample #1 can be upwardly convex as described above. On the other hand, the stress distribution in the first compression region CSR1 of sample #2 can be downwardly convex or substantially straight. In the stress distribution of the first compression region CSR1 of sample #1, the decrease in stress near the first surface US in the thickness direction from the first surface US is less than the decrease in stress near the first surface US in the thickness direction from the first surface US in the stress distribution of the first compression region CSR1 of sample #2. That is, since the stress decrease near the surface of sample #1 in the thickness direction from the surface of the glass article 100 is smaller than the stress decrease of sample #2, sample #1 can have a relatively large compressive stress.
[0150] exist Figure 7 In the first maximum compressive stress CS1 of sample #1 and the first maximum compressive stress CS1' of sample #2 are substantially equal at the first surface US, and the first compression depth DOC1 of sample #1 and the first compression depth DOC1' of sample #2 are substantially equal. However, the present invention is not limited to this case according to exemplary embodiments.
[0151] The maximum tensile stress CT1 in the tensile region CTR of sample #1 can be greater than the maximum tensile stress CT1' in the tensile region CTR of sample #2.
[0152] The stress distribution of the first compression region CSR1 of sample #1 will now be described in more detail. The stress distribution of the first compression region CSR1 of sample #1 may include a first point P1 and a first inflection point P2. The first inflection point P2 may be located between the first point P1 and the first surface US. The depth DOCa at the first point P1 may be between the first surface US and the first compression depth DOC1, and the stress CSa at the first point P1 may be between a stress value of 0 MPa and a first maximum compressive stress CS1 at the first surface US. The depth DOCt at the first inflection point P2 may be between the first surface US and the depth DOCa at the first point P1, and the stress CSa at the first inflection point P2 may be between the first maximum compressive stress CS1 at the first surface US and the stress CSa at the first point P1.
[0153] The depth DOCa at the first point P1 can be 45% to 55% of the first compressive depth DOC1 from the first surface US. In an exemplary embodiment, the stress CSa at the first point P1 can be greater than 50% of the first maximum compressive stress CS1 at the first surface US. For example, the stress CSa at the first point P1 can have a value of about 60% or more of the first maximum compressive stress CS1 at the first surface US. In an exemplary embodiment, the stress CSt at the first inflection point P2 can be 60% or more of the first maximum compressive stress CS1 at the first surface US.
[0154] For example, the first compression depth DOC1 can be in the range of 8 micrometers (μm) to 12 micrometers (μm).
[0155] For example, the first maximum compressive stress CS1 at the first surface US can be in the range of 800 MPa to 1100 MPa.
[0156] At a depth DOCa of the first point P1 within the range of 4 μm to 6 μm (within the range of the first compression depth DOC1), the glass article 100 may have a stress CSa of 400 MPa to 550 MPa, which is greater than 50% of the first maximum compressive stress CS1.
[0157] When the stress CSa at the depth DOCa of the first point P1 within the range of 4μm to 6μm (within the range of the first compression depth DOC1) of the glass article 100 exceeds 400MPa, it can prevent cracks or grooves from propagating to the tensile region CTR.
[0158] Furthermore, when the stress CSa at the depth DOCa of the first point P1 within the range of 4 μm to 6 μm (within the range of the first compression depth DOC1) of the glass article 100 is 550 MPa or less, the increased tensile region CTR according to the increased compression regions CSR1 and CSR2 can prevent cracks or grooves from propagating to the tensile region CTR, and thus prevent the glass article 100 from breaking and severely shattering.
[0159] A method for manufacturing a glass article 100 will now be described. In the exemplary embodiments described below, elements identical to those in the exemplary embodiments described above will be indicated by the same reference numerals, and their descriptions will be omitted or given briefly.
[0160] Figure 8 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment. Figure 9 It shows from Figure 8 A schematic diagram of a series of operations from cutting to tempering. Figure 10 Detailed Figure 9 High temperature / high humidity treatment operation. Figure 11 It is a graph showing the ion concentration around the surface of the glass article before the high temperature / high humidity treatment operation. Figure 12 It is a graph showing the ion concentration around the surface of a glass article after a high-temperature / high-humidity treatment operation.
[0161] Reference Figures 8 to 10 The method for manufacturing a glass article 100 according to an exemplary embodiment includes: molding operation (operation S1), cutting operation (operation S2), chamfering operation (operation S3), repair operation (operation S4), high temperature / high humidity treatment operation (operation S5), and chemical tempering operation (operation S6).
[0162] The molding operation (operation S1) may include: preparing the glass composition and molding the glass composition.
[0163] The glass composition may include a variety of compositions. In an exemplary embodiment, the glass composition may include lithium alumina-silicon (LAS) glass ceramics containing lithium aluminosilicate. For example, the glass composition may contain 50 to 80 mol% of SiO2, 1 to 30 mol% of Al2O3, 0 to 5 mol% of B2O3, 0 to 4 mol% of P2O5, 3 to 20 mol% of Li2O, 0 to 20 mol% of Na2O, 0 to 10 mol% of K2O, 3 to 20 mol% of MgO, 0 to 20 mol% of CaO, 0 to 20 mol% of SrO, 0 to 15 mol% of BaO, 0 to 10 mol% of ZnO, 0 to 1 mol% of TiO2, and 0 to 8 mol% of ZrO2. Here, "0 mol%" means substantially not containing the corresponding component. When a composition does not "substantially contain" a particular component, it means that the particular component was not intentionally included in the raw material, and includes cases where trace amounts (e.g., 0.1 mol% or less of impurities) are unavoidable.
[0164] Each component of the glass composition will now be described in more detail. SiO2 can be used to form the framework of the glass, increase chemical durability, and reduce crack growth due to scratches (i.e., indentations) on the glass surface. To fully exert the above effects, SiO2 can be included in an amount of 50 mol% or more. To exhibit sufficient solubility, SiO2 can be included in the glass composition in an amount of 80 mol% or less.
[0165] Al₂O₃ is used to improve the shatter resistance of glass. That is, when glass breaks, Al₂O₃ causes it to shatter into fewer fragments. Furthermore, Al₂O₃ acts as an active component, improving ion exchange properties during chemical tempering and increasing surface compressive stress after tempering. When included in amounts of 1 mol% or more, Al₂O₃ effectively performs these functions. To maintain the glass's acid resistance and fusibility, the Al₂O₃ content can be 30 mol% or lower.
[0166] B₂O₃ improves the shatter resistance and fusibility of glass. B₂O₃ can be omitted (i.e., 0 mol%), but when included in amounts of 0.5 mol% or more, it further improves the fusibility of the glass. 5 mol% or less of B₂O₃ can help suppress the formation of streaks during melting.
[0167] P2O5 improves ion exchange performance and brittleness. P2O5 can be omitted (i.e., 0 mol%), but when included in amounts of 0.5 mol% or more, P2O5 significantly performs the aforementioned functions. 4 mol% or less of P2O5 helps prevent a significant reduction in brittleness and acid resistance.
[0168] Li₂O is used to create surface compressive stress through ion exchange. Li ions near the glass surface can be exchanged for Ka ions via an ion exchange process. However, the amount of Li ions exchanged for Ka ions can be significantly less than the amount of Na ions exchanged for Ka ions. Li₂O can be further used to improve the fragility of glass.
[0169] Na₂O is used to create surface compressive stress and improve the fusibility of glass through ion exchange. Na ions located near the glass surface can be exchanged for K ions through an ion exchange process. The Na ion content can range from 10 wt% to 15 wt%. In the molding operation (operation S1), Na ions can be dispersed throughout the glass.
[0170] K₂O improves ion exchange performance and is associated with breakability. K₂O can be omitted, but it can be included in an amount of 0.5 mol% or more to improve ion exchange performance. The K₂O content used to prevent excessive reduction in breakability can be 10 mol% or less.
[0171] MgO is used to increase surface compressive stress and improve the breakability of chemically tempered glass. These effects are effectively achieved when the MgO content is 3 mol% or higher. MgO content of 20 mol% or lower helps reduce the likelihood of devitrification during glass melting.
[0172] CaO is used to improve the fusibility and brittleness of glass. CaO can be omitted, but 0.5 mol% or more of CaO can be included to effectively perform the above-mentioned functions. Since too high a CaO content may reduce ion exchange performance, an appropriate CaO content can be 20 mol% or lower.
[0173] Similar to CaO, SrO is used to improve the fusibility and brittleness of glass. SrO can be omitted, but 0.5 mol% or more of SrO can be included to effectively perform the aforementioned functions. Since too high a SrO content can reduce ion exchange performance, an appropriate SrO content can be 20 mol% or lower.
[0174] BaO is used to improve the fusibility and brittleness of glass. BaO can be omitted, but 0.5 mol% or more of BaO can be included to effectively perform the above-mentioned functions. A BaO content of 15 mol% or less can help prevent excessive degradation of ion exchange properties.
[0175] ZnO is used to improve the solubility of glass. ZnO can be omitted, but when it is included in an amount of 0.25 mol% or more, it can show a significant improvement in solubility. To prevent a decrease in weather resistance, the ZnO content can be kept at 10 mol% or lower.
[0176] TiO2 improves the breakability of chemically tempered glass. TiO2 can be omitted, but a significant improvement in breakability is observed when it is included in amounts of 0.1 mol% or more. To prevent devitrification during melting, 1 mol% or less of TiO2 can be included.
[0177] ZrO2 can increase surface compressive stress due to ion exchange and improve the glass's brittleness. ZrO2 can be omitted, but its effects are significant when present in amounts of 0.5 mol% or more. 8 mol% or less of ZrO2 helps suppress devitrification during melting.
[0178] If desired, in addition to the components listed above, the glass composition may also include components such as Y₂O₃, La₂O₃, Nb₂O₅, Ta₂O₅, and Gd₂O₃. The composition of the glass article 100 may be modified by a molding process or an ion exchange process, as described later.
[0179] Various methods can be used to mold glass compositions into the shape of flat glass. For example, glass compositions can be molded using a float process, a fusion draw process, or a slot draw process.
[0180] Glass molded into a flat shape can be cut using a cutting operation (operation S2). The glass molded into a flat shape can have dimensions different from those applied to the final glass article 100. For example, glass can be molded in a large-area substrate state as a mother substrate 10a1 comprising multiple glass articles, and then this glass can be cut into multiple glass units 10b1 to manufacture multiple glass articles. For example, although the final glass article 100 has a size of approximately 6 inches, the glass serving as the mother substrate 10a1 can be molded to a size several to several hundred times larger than the final glass article 100 (e.g., 120 inches), and then cut at once to manufacture 20 flat-shaped final glass articles 100. This improves processing efficiency compared to molding each glass article individually. Furthermore, even when glass corresponding to the size of a single glass article is molded, if the final glass article has various planar shapes, the desired shape can be formed through the cutting process.
[0181] The mother substrate 10a1 can be cut using a cutting blade 20, a cutting wheel, a laser, etc.
[0182] The glass cutting (operation S2) can be performed before the glass tempering (operation S6). The glass corresponding to the mother substrate 10a1 (hereinafter referred to as glass 10a1) can be tempered and then cut into units having the final glass article dimensions. However, in this case, since the cut surfaces of the glass (e.g., side surfaces) may not be tempered, it is desirable to perform the tempering operation (operation S6) after the cutting operation (operation S2) is completed.
[0183] In an exemplary embodiment, multiple mother substrates 10a1 can be cut together while they are stacked in the thickness direction. An adhesive layer (or bonding layer) AM can be inserted between adjacent mother substrates 10a1 in the thickness direction to bond them together. Figure 9 As shown, the dummy substrate 10a2 can be disposed at the top and bottom of the stacked structure of the mother substrate 10a1, respectively. The mother substrate 10a1 adjacent to the dummy substrate 10a2 located at the top and bottom can also be bonded to the dummy substrate 10a2 by an adhesive layer (or bonding layer) AM, respectively. That is, the mother substrate 10a1 and the dummy substrate 10a2 are stacked alternately.
[0184] Since multiple mother substrates 10a1 are cut together while they are stacked, the efficiency of the cutting process can be improved. Furthermore, the dummy substrates 10a2 respectively disposed at the top and bottom of the stacked structure of the mother substrates 10a1 prevent the surfaces of the glass units 10b1 (e.g., the upper and lower surfaces) from being undesirably treated with fluorine solution in the repair operation (operation S4) described later. In other words, the dummy substrates 10a2 respectively disposed at the top and bottom of the stacked structure of the mother substrates 10a1 can be used as barrier layers in subsequent processes of the mother substrates 10a1.
[0185] Next, the glass units 10b1 cut from each mother substrate 10a1 are chamfered (operation S3). More specifically, chamfered surfaces CHS1 and CHS2 are formed for each glass unit 10b1 in a stacked structure where the glass units 10b1 and the dummy substrate units 10b2 are bonded to each other by an adhesive layer (or bonding layer) AM inserted between them. The chamfering of the glass units 10b1 (operation S3) can be achieved by computer numerical control (CNC). Since the shape of each of the chamfered surfaces CHS1 and CHS2 of each chamfered glass unit 10b1 has been described above, its detailed or redundant description will be omitted. The chamfering of each glass unit 10b1 prevents the edges of the glass units 10b1 from peeling off due to breakage or impact.
[0186] Next, the chamfered glass unit 10b1 is repaired (or surface treated) (operation S4). More specifically, the chamfered glass unit 10b1 is repaired (operation S4) to improve the reduced strength of the side portion of the glass unit 10b1 in a stacked structure where the glass unit 10b1 and the dummy substrate unit 10b2 are bonded to each other using an adhesive layer (or bonding layer) AM inserted between them. The chamfered glass units 10b1 stacked in the thickness direction can be repaired together (operation S4).
[0187] The chamfered glass unit 10b1 can be repaired using repair solution 40 (operation S4). Repair solution 40 can be a solution containing fluoride ions.
[0188] In the repair of glass unit 10b1 (operation S4), the dummy substrate units 10b2 further provided at the top and bottom of the stacked structure of glass unit 10b1 can prevent the surfaces of glass unit 10b1 (e.g., the upper and lower surfaces) from being undesirably treated with fluorine solution.
[0189] In some exemplary embodiments, the glass unit 10b1 may be further polished between the chamfering (operation S3) and the repair (operation S4) of the glass unit 10b1.
[0190] Next, sodium ions are concentrated on the surface of glass unit 10b1. In an exemplary embodiment, concentrating sodium ions on the surface of glass unit 10b1 includes a high-temperature / high-humidity treatment operation (operation S5). After glass unit 10b1 repair (operation S4), the glass units 10b1 stacked in the thickness direction can be separated, and then the glass units 10b1 are treated with high temperature / high humidity (operation S5). The high-temperature / high-humidity treatment of glass unit 10b1 (operation S5) can be performed for about 2 to 4 hours by placing the separated glass unit 10b1 in a slot of the support device 50 inside the chamber CH and adjusting the interior of the chamber CH to a temperature condition of about 80 to about 90 degrees Celsius and a humidity condition of about 80% to about 90%.
[0191] Under the above temperature and humidity conditions, the hydrogen ions (H+) in the humid air inside the room CH + ) or hydrated hydrogen (H3O) + Hydrogen ions (H+) are adsorbed onto the first surface US and the second surface RS of glass unit 10b1. + ) or hydrated hydrogen (H3O) + Sodium ions tend to replace easily replaceable ions, and these easily replaceable sodium ions can migrate to the first surface US and the second surface RS of glass unit 10b1. Some of the sodium ions that have migrated to the first surface US and the second surface RS of glass unit 10b1 can be adsorbed hydrogen ions (H+).+ ) or hydrated hydrogen (H3O) + Other sodium ions that have migrated to the first surface US and the second surface RS of glass unit 10b1 can remain on the first surface US and the second surface RS of glass unit 10b1, instead of being adsorbed by hydrogen ions (H). + ) or hydrated hydrogen (H3O) + )replace.
[0192] In other words, the high temperature / high humidity treatment of glass unit 10b1 can lead to the formation of sodium ion excess regions near the first surface US and the second surface RS of each glass unit 10b1.
[0193] exist Figure 11 and Figure 12 In the diagram, the x-axis represents the thickness direction from the first surface US or the second surface RS, and the y-axis represents the content (atomic %) of each ion (sodium, calcium, carbon, silicon, oxygen).
[0194] Reference Figure 11 and Figure 12 It can be seen that the high temperature / high humidity treatment (operation S5) of glass unit 10b1 increases the distribution of sodium ions near the surface US and RS of glass unit 10b1.
[0195] Next, the glass unit 10b1 is tempered (operation S6). The ion exchange process can be performed once or multiple times. For example, the ion exchange process can be performed as a single ion exchange process. A single ion exchange process can be performed in a bath. A single ion exchange process can be performed simultaneously on multiple glass units 10b1. That is, multiple glass units 10b1 can be immersed in a bath, so that ion exchange can occur simultaneously in the glass units 10b1.
[0196] A primary ion exchange process is a process of providing each glass cell 10b1 with a first compression depth DOC1 and a second compression depth DOC2. The glass cell 10b1 is exposed to a single soluble salt containing potassium ions or a mixed soluble salt containing potassium and sodium ions. For example, in a primary ion exchange process, the glass cell 10b1 is immersed in a bath containing a single soluble salt containing potassium nitrate or a mixed soluble salt containing potassium nitrate and sodium nitrate. When using a mixed soluble salt, the potassium nitrate content in the bath may be much greater than the sodium nitrate content. For example, the potassium nitrate to sodium nitrate salt ratio can be adjusted in the range of 95:5 to 99:1. In an exemplary embodiment, the potassium nitrate to sodium nitrate salt ratio in the mixed soluble salt of the primary ion exchange process may be 99:1.
[0197] A single ion exchange process can be carried out at, for example, a temperature of about 420 degrees Celsius or higher.
[0198] The single ion exchange process converts sodium ions in each glass unit 10b1 into potassium ions, which are larger than sodium ions, thereby increasing the concentration of potassium ions in the glass unit 10b1.
[0199] Furthermore, the sodium ion excess region formed near the first surface US and the second surface RS of each glass unit 10b1 through the high-temperature / high-humidity treatment (operation S5) of the glass unit 10b1 can further promote ion exchange between potassium ions and sodium ions at the first surface US and the second surface RS of each glass unit 10b1, and can lead to, for example Figure 7 The stress distribution curves of the samples #1 and #2 to be formed, as described in the figure.
[0200] The glass article 100_1 according to an exemplary embodiment will now be described.
[0201] Figure 13 This is a cross-sectional view of a flat glass article 100_1 according to an exemplary embodiment. Figure 14 It is a graph showing the stress distribution of the glass article 100_1 according to an exemplary embodiment.
[0202] Reference Figure 13 and Figure 14 According to the present exemplary embodiment, the glass article 100_1 and Figure 3 and Figure 7 The difference between the glass article 100 and the glass article 100_1 according to the present exemplary embodiment is that the compressive stress at the first compression region CSR1_1 and the second compression region CSR2_1 is greater than that of the glass article 100_1. Figure 3 and Figure 7 The first maximum compressive stress CS1 and the second maximum compressive stress CS2 at the first surface US and the second surface RS of the glass article 100, and the first compression depth DOC1_1 and the second compression depth DOC2_1 of the glass article 100_1 according to the present exemplary embodiment are less than Figure 3 and Figure 7 The first compression depth DOC1 and the second compression depth DOC2 of the glass article 100.
[0203] More specifically, the first maximum compressive stress CS1_1 at the first surface US of the glass article 100_1 (sample #3) according to the current exemplary embodiment may be greater than the first maximum compressive stress CS1' at the first surface US of the sample #2, and the first compression depth DOC1_1 of the glass article 100_1 (sample #3) according to the current exemplary embodiment may be less than the first compression depth DOC1' of the sample #2.
[0204] The maximum tensile stress CT1_1 in the tensile region CTR of sample #3 may be greater than the maximum tensile stress CT1' in sample #2 in absolute value.
[0205] The glass article 100_1 according to the present exemplary embodiment may also include impurities. The content of the impurities may be 0.02 wt% or more. The impurities may include copper ions, iron ions or tin ions.
[0206] A method for manufacturing a glass article 100_1 according to the present exemplary embodiment will now be described.
[0207] Figure 15 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment. Figure 16 Detailed explanation based on Figure 15 The heat treatment operation of an exemplary embodiment. Figure 17 yes Figure 16 A magnified view of region A. Figure 18 It is a graph showing the distribution of sodium ions before and after the heat treatment operation according to an exemplary embodiment. Figure 19 It is a graph showing the distribution of potassium ions during tempering before and after the heat treatment operation according to an exemplary embodiment.
[0208] Reference Figures 15 to 19 The method for manufacturing glass article 100_1 according to the present exemplary embodiment and according to Figure 8 The difference in the method of manufacturing glass article 100 of the exemplary embodiment is that heat treatment (operation S5_1) is performed instead of Figure 8 High temperature / high humidity treatment (operation S5) of an exemplary embodiment.
[0209] In operation S5_1, multiple glass plates 10b1_1 can be placed in the slots of the support device 50_1 within chamber CH_1. The glass plates 10b1_1 can be heat-treated (operation S5_1) in chamber CH_1 at a temperature of approximately 600 to 700 degrees Celsius, above the strain point and below the softening point of glass, for less than approximately 4 hours, during which an oxidizing atmosphere (containing oxygen molecules) is generated in chamber CH_1.
[0210] Under the aforementioned temperature conditions in chamber CH_1, impurities such as copper ions, iron ions, or tin ions disposed on surfaces US and RS of each glass slide 10b1_1 can be oxidized within chamber CH_1. To achieve electronic balance in the oxidation of impurities, sodium ions can migrate to the first surface US and the second surface RS of each glass slide 10b1_1.
[0211] In other words, the heat treatment of glass plate 10b1_1 (operation S5_1) can cause the formation of sodium ion excess regions near the first surface US and the second surface RS of each glass plate 10b1_1, thereby further promoting ion exchange between potassium ions and sodium ions at the first surface US and the second surface RS of each glass plate 10b1_1, and forming the regions shown above. Figure 14 The stress distribution curves of samples #3 and #2 described in the figure.
[0212] exist Figure 18 and Figure 19 In the diagram, the x-axis represents the thickness direction from the first surface US or the second surface RS of the glass slide 10b1_1, and the y-axis represents the distribution of sodium ions and potassium ions.
[0213] Reference Figure 18 The distribution of sodium ions near the surface US or RS after heat treatment (operation S5_1) may be greater than the distribution of sodium ions near the surface US or RS before heat treatment (operation S5_1), and the distribution of potassium ions near the surface US or RS after heat treatment (operation S5_1) may be greater than the distribution of sodium ions near the surface US or RS before heat treatment (operation S5_1).
[0214] In addition, refer to Figure 19 After heat treatment (operation S5_1) and chemical tempering (operation S6), the distribution of potassium ions near the surface US or RS can be greater than the distribution of potassium ions near the surface US or RS after chemical tempering (operation S6) without heat treatment (operation S5_1).
[0215] Figure 20 This is a cross-sectional view of a glass article 104 according to an exemplary embodiment. Figure 21 yes Figure 20 Enlarged sectional view. Figure 22 This is a graph showing the stress distribution of the glass article 104 according to an exemplary embodiment. Although for ease of description... Figure 20 Glassware 104 Figure 21 It is shown as flat, but glass article 104 is actually as shown. Figure 20 The image shown is folded.
[0216] Reference Figures 20 to 22The foldable glass article 104 differs from the flat glass article 100 in that a tensile force TS is formed on the outer peripheral surface (i.e., the first surface US), and a compressive force CS is further formed on the inner peripheral surface (i.e., the second surface RS). That is, even if sufficient compressive stress is formed on the outer peripheral surface US of the foldable glass article 104 through chemical tempering, the compressive stress may be offset by the tensile force TS generated by folding the glass article 104. On the other hand, the compressive stress formed on the inner peripheral surface RS may be enhanced by the compressive force CS generated by folding the glass article 104. Therefore, cracks or grooves may easily form around the outer peripheral surface US, where the compressive stress is offset by the tensile force TS, and may easily propagate to the tensile region CTR. Further reference Figure 2 The glass product 104 can be bonded to the display panel 200 via the optically transparent adhesive layer 300. When the foldable glass product 104 is bonded to the display panel 200 via the optically transparent adhesive layer 300, the display panel 200, the optically transparent adhesive layer 300, and the foldable glass product 104 can be collectively referred to as a foldable display device.
[0217] In this case, the inner peripheral surface RS can be directly attached to the optically transparent adhesive layer 300, and the outer peripheral surface US can be located outside the inner peripheral surface RS.
[0218] like Figure 20 As shown, the foldable display device can be folded so that portions of the inner peripheral surfaces RS face each other. As described above, a tensile force TS can be applied to the outer peripheral surface US.
[0219] The first compression depth DOC1_2 of the first compression region CSR1_2, including the outer peripheral surface US, can be greater than the second compression depth DOC2_2 of the second compression region CSR2_2, including the inner peripheral surface RS. The first maximum compressive stress CS1_2 at the outer peripheral surface US of the first compression region CSR1_2 can be greater than the second maximum compressive stress CS2_2 at the inner peripheral surface RS of the second compression region CSR2_2.
[0220] In other words, based on Figure 22In the current exemplary embodiment of the glass article 104, the stress distribution function f(x)' of the first compression region CSR1_2 and the stress distribution of the second compression region CSR2_2 may be asymmetrical to each other. More specifically, the first compression depth DOC1_2 of the first compression region CSR1_2, including the outer peripheral surface US, may be greater than the second compression depth DOC2_2 of the second compression region CSR2_2, including the inner peripheral surface RS. The first maximum compressive stress CS1_2 at the outer peripheral surface US of the first compression region CSR1_2 may be greater than the second maximum compressive stress CS2_2 at the inner peripheral surface RS of the second compression region CSR2_2.
[0221] Furthermore, the stress distribution in the first compression region CSR1_2 may bulge upwards. On the other hand, the stress distribution in the second compression region CSR2_2 may bulge downwards or be substantially straight. The decrease in stress in the first compression region CSR1_2 from the first surface (outer peripheral surface) US in the thickness direction may be less than the decrease in stress in the second compression region CSR2_2 from the second surface (inner peripheral surface) RS in the thickness direction. That is, since the first compression region CSR1_2 has a smaller stress decrease in the thickness direction from the surface of the glass article 104 than the second compression region CSR2_2, and as described above, has a greater compression depth and a greater compressive stress at the surface, the first compression region CSR1_2 may have relatively greater compressive energy.
[0222] The stress distribution in the first compression region CSR1_2 and the stress distribution in the second compression region CSR2_2 can be generated by the method of manufacturing the glass article 104, which will be described later.
[0223] Figure 23 This is a flowchart illustrating operations in a method for manufacturing glass articles according to an exemplary embodiment. Figure 24 Detailed explanation based on Figure 23 An exemplary embodiment of the electric field application operation. Figure 25 yes Figure 24 A magnified view of region B.
[0224] Reference Figures 23 to 25 The method of manufacturing glass article 104 according to the present exemplary embodiment and according to Figure 8 The difference in the method of manufacturing glass article 100 of the exemplary embodiment is that an electric field application operation (operation S5_2) is performed instead of a high temperature / high humidity treatment operation (operation S5).
[0225] More specifically, an electric field can be applied to the glass plate 10b1_2 after it has been repaired (operation S4) (operation S5_2). Then, chemical tempering can be performed (operation S6).
[0226] The application of an electric field (operation S5_2) can be performed using an electric field application device 50_2, which includes a positive plate electrode AE (or anode) to which a positive voltage is applied and a negative plate electrode CE (or cathode) to which a negative voltage is applied in chamber CH_2. Each glass plate 10b1_2 is placed between the positive plate electrode AE and the negative plate electrode CE. Here, a negative voltage can be applied to a first surface US (i.e., the outer peripheral surface) of the glass plate 10b1_2, and a positive voltage can be applied to a second surface RS (i.e., the inner peripheral surface).
[0227] Each of the negative electrode CE and the positive electrode AE may include a conductive material with a flat surface. For example, the conductive material may be a metal, a transparent oxide conductive material (such as ITO), or a conductive polymer.
[0228] During the application of an electric field, the CH2 chamber can maintain a constant temperature. In another exemplary embodiment, the CH2 chamber can freely adjust the range of the applied electric field temperature. For example, during the application of an electric field, the internal temperature of the CH2 chamber can be adjusted within a range of about 0 degrees Celsius to about 400 degrees Celsius. When the internal temperature increases during the application of an electric field, the migration rate of sodium ions (i.e., alkali ions) can increase.
[0229] The magnitude of the electric field applied to the glass plate 10b1_2 can range from 100 volts / cm (V / cm) to 200 V / cm.
[0230] In some exemplary embodiments, the electric field can be applied to the glass sheet 10b1_2 in a silicone oil bath instead of in chamber CH_2. In this case, the electric field can be applied to the glass sheet 10b1_2 while all surfaces and side surfaces of the glass sheet 10b1_2 are immersed in the silicone oil bath.
[0231] Sodium ions adjacent to the positive voltage substrate (i.e., the positive electrode AE) may behave differently from sodium ions adjacent to the negative voltage substrate (i.e., the negative electrode CE). Since sodium ions adjacent to the positive voltage substrate (positive electrode AE) have the same polarity as the anode, they can migrate towards the negative voltage substrate (negative electrode CE). However, since sodium ions adjacent to the negative voltage substrate (negative electrode CE) have a different polarity than the cathode, they remain adjacent to the negative voltage substrate (negative electrode CE). Therefore, the distribution (amount) of sodium ions migrating towards the negative voltage substrate (negative electrode CE) can increase, thereby forming an excess sodium ion region in the first surface US (outer peripheral surface) of the glass slide 10b1_2.
[0232] In other words, applying an electric field to the glass plate 10b1_2 (operation S5_2) can cause the formation of a sodium ion excess region near the first surface US (outer peripheral surface) of the glass plate 10b1_2, thereby further promoting ion exchange between potassium ions and sodium ions at the first surface US (outer peripheral surface) of the glass plate 10b1_2 and forming the region as described above. Figure 22 The stress distribution shown is illustrated.
[0233] Figure 26 The electric field application operation performed according to the exemplary embodiment using the electric field application device 50_2a according to the exemplary embodiment is shown in detail. Figure 27 This illustrates a glass placement operation performed using an electric field application device 50_2a according to an exemplary embodiment, during an electric field application operation according to an exemplary embodiment. Figure 28 The movement of the electric field applying device 50_2a according to an exemplary embodiment is shown.
[0234] Reference Figures 26 to 28 According to the exemplary embodiment, the electric field application operation and Figure 23 and Figure 24 The difference in the electric field application operation is that the electric field application operation according to the exemplary embodiment is performed by the electric field application device 50_2a according to the exemplary embodiment.
[0235] The electric field application operation according to the current exemplary embodiment may further include: placing a plurality of glass plates 10b1_2 between a plurality of negative electrode plates CE and a plurality of positive electrode plates AE. The negative electrode plates CE and the positive electrode plates AE may be arranged alternately. For example, as... Figure 26 As shown, the negative electrode CE and the positive electrode AE can be arranged alternately along the horizontal direction. When placing the glass plate 10b1_2, the glass plate 10b1_2 can be placed between the alternately arranged negative electrode CE and positive electrode AE.
[0236] Reference Figure 27 The negative electrode CE and the positive electrode AE can be rotatable. For example, each of the negative electrode CE and the positive electrode AE of the electric field applying device 50_2a is rotatable so that it extends horizontally during the glass placement operation and vertically when an electric field is applied after the glass placement operation. Therefore, when an electric field is applied to the glass sheet 10b1_2 with the glass sheet inserted between the horizontally extending negative electrode CE and positive electrode AE, the glass sheet 10b1_2 can be prevented from warping in the thickness direction.
[0237] Reference Figure 28Each of the negative electrode CE and the positive electrode AE can be moved horizontally or vertically. Therefore, the glass plate 10b1_2 can be more easily placed between the negative electrode CE and the positive electrode AE.
[0238] Each of the negative and positive voltages may include a direct current (DC) waveform, an alternating current (AC) waveform, a pulsed DC waveform, or a periodic AC (radio frequency (RF)) waveform.
[0239] The electric field applying device 50_2a according to an exemplary embodiment may further include a heat supply line HL connected to the negative electrode CE and the positive electrode AE, respectively, to provide heat. The heat supply line HL can be used to apply an electric field and provide heat simultaneously. The heat supply line HL can be connected to or inserted into the surface or interior of the negative electrode CE and the positive electrode AE, respectively. After applying an electric field through the heat supply line HL, the tempering rate during surface tempering can be increased, and thermal annealing can be performed.
[0240] Figure 29 The electric field application operation performed using the electric field application device 50_2b according to an exemplary embodiment is shown in detail.
[0241] Reference Figure 29 The electric field applying device 50_2b according to the exemplary embodiment differs from the electric field applying device 50_2a in that the electric field applying device 50_2b further includes a coating CT disposed on the surface of each negative electrode CE_1 facing the adjacent positive electrode AE_1 and on the surface of each positive electrode AE_1 facing the adjacent negative electrode CE_1.
[0242] Coated CT may include electrode materials.
[0243] Figure 30 The electric field application operation performed using the electric field application device 50_2c according to an exemplary embodiment is shown in detail.
[0244] Reference Figure 30 According to an exemplary embodiment, the electric field applying device 50_2c and Figure 29 The difference between the electric field application device 50_2b and the coating CT_1 is that the coating CT_1 includes an electrode protective layer.
[0245] More specifically, the coating CT_1 of the electric field applying device 50_2c according to the exemplary embodiment may include an electrode protective layer. The electrode protective layer may include, but is not limited to, a dielectric.
[0246] Figure 31 The electric field application operation performed using the electric field application device 50_2d according to an exemplary embodiment is shown in detail.
[0247] Reference Figure 31According to an exemplary embodiment, the electric field applying device 50_2d and the glass placement operation are as follows: Figure 26 The difference between the electric field application device 50_2a and the glass placement operation is that, in the glass placement operation, a negative electrode CE and a positive electrode AE are provided, and a plurality of glass sheets 10b1_2 are arranged parallel to each other between the negative electrode CE and the positive electrode AE.
[0248] More specifically, the electric field applying device 50_2d according to an exemplary embodiment may include a negative electrode CE and a positive electrode AE. A plurality of glass plates 10b1_2 may be arranged parallel to each other between the negative electrode CE and the positive electrode AE.
[0249] The electric field applying device 50_2d according to the present exemplary embodiment may further include a glass protective layer SPL disposed between the negative electrode CE and the positive electrode AE. Each of the glass protective layers SPL may be disposed between adjacent glass sheets 10b1_2. Each of the glass protective layers SPL can prevent adjacent glass sheets 10b1_2 from being physically damaged, such as by scratching each other. The glass protective layer SPL may include a film or a resin.
[0250] The glass articles and display devices according to exemplary embodiments may have good compressive stress while having a small thickness.
[0251] According to the method for manufacturing glass articles based on exemplary embodiments, glass articles having good compressive stress and small thickness can be manufactured.
[0252] According to the electric field application device of the exemplary embodiment, glass articles with good compressive stress and small thickness can be manufactured.
[0253] Although exemplary embodiments of the invention have been disclosed for illustrative purposes, those skilled in the art will understand that various modifications, additions, and substitutions are possible without departing from the scope and spirit of the invention as disclosed in the appended claims.
Claims
1. Glassware, including: First surface; The second surface is opposite to the first surface; A first compression region extends from the first surface to a first compression depth in the thickness direction of the glass article; A second compression region extends from the second surface to a second compression depth in the thickness direction; as well as The stretching region is positioned between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The thickness of the glass article is 0.01 to 0.05 mm. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
2. The glass article as described in claim 1, wherein, When the stress distribution is shown as a graph with the x-axis representing the thickness direction and the y-axis representing the stress value, the stress distribution in the first compression region bulges upward.
3. The glass article as described in claim 2, wherein, The first compression depth is in the range of 8µm to 12µm, and the compressive stress at the first surface is in the range of 800MPa to 1100MPa.
4. The glass article as described in claim 3, further comprising: A first side surface is located between the first surface and the second surface; The first chamfered surface is located between the first side surface and the first surface; as well as The second chamfered surface is located between the first side surface and the second surface.
5. The glass article as described in claim 3, wherein, The stress distribution in the first compression region is symmetrical to the stress distribution in the second compression region.
6. The glass article as described in claim 5 further comprises hydrogen ions and hydrated hydrogen ions.
7. The glass article of claim 5 further includes impurities, wherein the content of the impurities is 0.02 wt% or higher, and the impurities contain copper ions, iron ions or tin ions.
8. The glass article as described in claim 3, wherein, The first compression depth of the first compression region is greater than the second compression depth of the second compression region, and the magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface.
9. Glass articles, including: First surface; The second surface is opposite to the first surface; A first compression region extends from the first surface to a first compression depth in the thickness direction of the glass article; A second compression region extends from the second surface to a second compression depth in the thickness direction; as well as The stretching region is positioned between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The first compression depth of the first compression region is greater than the second compression depth of the second compression region. The magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface. The thickness of the glass product is 0.01 to 0.05 mm. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
10. The glass article as claimed in claim 9, wherein, The glass article is formed sequentially by an electric field application operation and a chemical tempering operation, wherein a negative voltage is applied to the first surface and a positive voltage is applied to the second surface during the electric field application operation.
11. A display device, including: The display panel includes multiple pixels; A cover window is mounted on the display panel; as well as An optically transparent adhesive layer is disposed between the display panel and the cover window. The cover window includes: First surface; The second surface is opposite to the first surface; A first compression region extends from the first surface to a first compression depth in the thickness direction of the cover window; A second compression region extends from the second surface to a second compression depth in the thickness direction; and The stretching region is positioned between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The thickness of the cover window is 0.01 to 0.05 mm. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
12. The display device as claimed in claim 11, wherein, When the stress distribution is shown as a graph with the x-axis representing the thickness direction and the y-axis representing the stress value, the stress distribution in the first compression region bulges upward, the first compression depth is in the range of 8µm to 12µm, and the compressive stress at the first surface is in the range of 800MPa to 1100MPa.
13. The display device as claimed in claim 12, wherein, The first compression depth of the first compression region is greater than the second compression depth of the second compression region, and the magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface.
14. A method for manufacturing glass articles, the method comprising: Form a glass sheet with a thickness of 0.01 to 0.05 mm; This causes sodium ions to concentrate on the surface of the glass slide; as well as The glass sheet having sodium ions concentrated on the surface of the glass sheet is chemically tempered to obtain the glass article; The glass products include: First surface; and A first compression region extends from the first surface to a first compression depth in the thickness direction of the glass article; The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
15. The method of claim 14, wherein, Concentrating the sodium ions on the surface of the glass slide includes a high-temperature / high-humidity treatment performed under temperature conditions of 80 to 90 degrees Celsius, humidity conditions of 80 to 90%, and a duration of 4 hours or less.
16. The method of claim 14, wherein, Concentrating the sodium ions on the surface of the glass slide includes heat treatment performed at a temperature of 600 to 700 degrees Celsius for 4 hours or less.
17. The method of claim 14, wherein, The surface of the glass sheet includes a first surface and a second surface opposite to the first surface, and the concentration of sodium ions on the surface of the glass sheet includes an electric field application operation in which a negative voltage is applied to the first surface and a positive voltage is applied to the second surface.
18. The method of claim 17, wherein, In the electric field application operation, an electric field is applied to the glass plate in a temperature-controlled room.
19. The method of claim 18, wherein, During the electric field application operation, the internal temperature of the chamber is in the range of 0 to 400 degrees Celsius, and the magnitude of the electric field applied during the electric field application operation is in the range of 100 V / cm to 200 V / cm.
20. The method of claim 17, wherein, In the electric field application operation, an electric field is applied to the glass slide in a silicone oil bath.
21. A method for manufacturing glass articles, the method comprising: A glass sheet is formed, the glass sheet including a first surface and a second surface opposite to the first surface, and having a thickness of 0.01 to 0.05 mm; An electric field application operation is performed, in which a negative voltage is applied to the first surface and a positive voltage is applied to the second surface; as well as The glass sheet is chemically tempered to obtain the glass product; The glass products include: First surface; and A first compression region extends from the first surface to a first compression depth in the thickness direction of the glass article; The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
22. The method of claim 21, wherein, The electric field application operation is performed using an electric field application device, which includes a negative plate electrode that applies the negative voltage to the first surface and a positive plate electrode that applies the positive voltage to the second surface.
23. The method of claim 22, wherein, In the electric field application operation, an electric field is applied to the glass slide in a temperature-controlled room. During the application of the electric field, the temperature inside the room is in the range of 600 degrees Celsius to 700 degrees Celsius, and In the electric field application operation, the magnitude of the applied electric field is in the range of 100V / cm to 200V / cm.
24. The method of claim 22, wherein, The heat supply lines are connected to the negative electrode and the positive electrode respectively to provide heat.
25. The method of claim 22, wherein, The electric field application operation also includes: The glass plate is placed between the negative electrode and the positive electrode. The negative electrode, the positive electrode, and the glass sheet are each configured in multiple ways. The negative electrode and the positive electrode are arranged alternately, and when placing the glass sheet, the glass sheet is placed between the alternately arranged negative electrode and the positive electrode.
26. The method of claim 25, wherein, Each of the negative and positive electrode plates of the electric field applying device is rotatable, thereby extending horizontally during the placement of the glass plate and vertically when an electric field is applied after the glass plate is placed.
27. The method of claim 26, wherein, Each of the negative electrode and the positive electrode is movable along the horizontal direction or the vertical direction.
28. The method of claim 22, wherein, The electric field application operation also includes: The glass plate is placed between the negative electrode and the positive electrode. Each of the negative electrode plate and the positive electrode plate is provided as a single one, and multiple glass sheets are provided, wherein the glass sheets are arranged parallel to each other between the negative electrode plate and the positive electrode plate when they are placed.
29. The method of claim 22, wherein, Each of the negative voltage and the positive voltage includes a DC waveform, an AC waveform, a pulsed DC waveform, or an RF waveform.
30. Glass articles, including: First surface; The second surface is opposite to the first surface; A first compression region extends from the first surface to a first compression depth in the thickness direction of the glass article; A second compression region extends from the second surface to a second compression depth in the thickness direction; as well as The stretching region is positioned between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The stress distribution in the first compression region is asymmetrical with that in the second compression region. Furthermore, the magnitude of the compressive stress at the first surface is different from that at the second surface. The thickness of the glass product is 0.01 to 0.05 mm. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
31. The glass article as claimed in claim 30, wherein, The magnitude of the compressive stress at the first surface is greater than the magnitude of the compressive stress at the second surface.
32. The glass article as claimed in claim 31, wherein, The first compression depth of the first compression region is greater than the second compression depth of the second compression region.
33. A display device, including: The display panel includes multiple pixels; A cover window is mounted on the display panel; as well as An optically transparent adhesive layer is disposed between the display panel and the cover window. The cover window includes: First surface; The second surface is opposite to the first surface; A first compression region extends from the first surface to a first compression depth in the thickness direction of the cover window; A second compression region extends from the second surface to a second compression depth in the thickness direction; and The stretching region is positioned between the first compression region and the second compression region. The stress distribution in the first compression region includes a first point and a first inflection point. The first inflection point is located between the first point and the first surface. The depth from the first surface to the first point is 45% to 55% of the first compression depth from the first surface. The stress at the first point is greater than 50% of the compressive stress at the first surface. The stress distribution in the first compression region is asymmetrical with that in the second compression region. The magnitude of the compressive stress at the first surface is greater than that at the second surface. The second surface contacts the optically transparent adhesive layer, and the first surface is located outside the second surface. The thickness of the cover window is 0.01 to 0.05 mm. The stress at the first inflection point is 60% or more of the compressive stress at the first surface.
34. The display device as claimed in claim 33, in, The display device is foldable, and When operated in a folded state, the display device is folded such that portions of the second surface face each other and a tensile force is applied.
35. The display device as claimed in claim 34, wherein, The first compression depth of the first compression region is greater than the second compression depth of the second compression region.
Citation Information
Patent Citations
Heat recovery apparatus and method
KR1020200000881A
Patterned ion-exchanged substrates and methods for making the same
CN107001123A
S-shaped stress profiles and methods of making
CN108367964A
Asymmetric chemical strengthening
US20190023611A1
